Gambaran Penyakit Komorbid dan Mortalitas Pada Pasien Hemodialisis Terkonfirmasi COVID-19 di RSUD Koja - Afifah Arum Meylany (2021)
Hypertension and diabetes mellitus are often found in hemodialysis patients with end-stage chronic kidney disease. However, it is possible to hemodialysis patients have more comorbidities and they have a relationship with mortality patients. Moreover the COVID-19 patients with comorbidities have an increased risk of illness and death. Therefore, it is necessary to control comorbidities during the COVID-19 outbreak. The purpose of the study is identify of comorbidity and mortality hemodialysis patients with COVID-19 at Koja Hospital. This study is a descriptive with a retrospective single study and univariate analysis. The total of samples is 45 hemodialysis patients with COVID-19. The results of this study showed the mean age of hemodialysis patients with COVID-19 are 50 years and the majority are women without contact with COVID-19 patients. They are generally having two comorbidities (53.3%). Hypertension, cardiovascular disease and anemia are common comorbidities among patients. In addition, dyspnea (14,21%), tachycardia (13,71%), and cough (12,69%) were common as clinical manifestations of COVID-19. Meanwhile, the low oxygen saturation and weak of pulse (15,52%) were found in mortality patients. On other the parameters, temperature, blood pressure, respiratory rate, hemoglobin, BUN, and creatinine were found be abnormal.